2005
DOI: 10.1186/ar1772
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal stress axis function and the relationship with chronic widespread pain and its antecedents

Abstract: In clinic studies, altered hypothalamic-pituitary-adrenal (HPA) axis function has been associated with fibromyalgia, a syndrome characterised by chronic widespread body pain. These results may be explained by the associated high rates of psychological distress and somatisation. We address the hypothesis that the latter, rather than the pain, might explain the HPA results. A population study ascertained pain and psychological status in subjects aged 25 to 65 years. Random samples were selected from the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(43 citation statements)
references
References 21 publications
5
35
2
1
Order By: Relevance
“…No significant associations with chronic multi-site musculoskeletal pain were found for the dynamic of the cortisol awakening response (AUCi) and post-dexamethasone cortisol levels, which is in contrast to a previous study that demonstrated non-suppression of the HPA-axis in 131 subjects with chronic widespread pain by elevated serum cortisol levels after a 0.25 mg dexamethasone suppression test [25]. This opposite finding might be explained by heterogeneity of samples or measurement differences, e.g.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…No significant associations with chronic multi-site musculoskeletal pain were found for the dynamic of the cortisol awakening response (AUCi) and post-dexamethasone cortisol levels, which is in contrast to a previous study that demonstrated non-suppression of the HPA-axis in 131 subjects with chronic widespread pain by elevated serum cortisol levels after a 0.25 mg dexamethasone suppression test [25]. This opposite finding might be explained by heterogeneity of samples or measurement differences, e.g.…”
Section: Discussioncontrasting
confidence: 98%
“…However, in support of our findings, a cross-sectional study by McBeth et al showed that a lower saliva cortisol score, composed of morning and evening cortisol levels, was associated with chronic widespread pain and being psychologically at risk of chronic widespread pain [25]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, previous studies have not been able to directly test the hypothesis that low nSES affects adverse health outcomes by altering stress system function. In this study, a common genetic polymorphism near FKBP5 , a gene known to influence the function of the HPA axis [4; 6; 27; 39; 49; 56], moderated MSP outcomes among those living in the lowest quartile of nSES, but not among individuals in less disadvantaged environments. Indeed, although average differences in pain across all time-points between the least and most disadvantaged quartiles of nSES (decrease of 0.6 points on 0-10 NRS or 14% decrease) did not exceed clinical significance (decrease of 1.7 points or 28% decrease [17]), differences according to SNP rs2817038 allele in the most disadvantaged nSES quartile (2.0 points on NRS or 42% decrease) were clinically significant.…”
Section: Discussionmentioning
confidence: 83%
“…Specific polymorphisms of genes codifying for serotonin transporters and the catechol-O-methyltransferase enzyme which inactivates catecholamines, neurotransmitters implicated in the pathogenesis of affective disorders, have been associated with FM [5]. It has however been acknowledged that the clinical picture of FM often overlaps with those of the Chronic Fatigue Syndrome and Irritable Bowel Syndrome: response to stress is considered to play a crucial role in the pathogenesis of these disorders [6,7]. But the efficacy of antidepressants in this group of disorders may be related to the analgesic effect of these drugs rather that their antidepressant effect and appears strongest in agents with mixed-receptor or predominantly noradrenergic activity, rather than serotoninergic activity [8]…”
Section: Introductionmentioning
confidence: 99%